This preview shows page 1. Sign up to view the full content.
Unformatted text preview: x-1 (b) f ( x ) = x 2 + x + x-1 + x-2 (c) f ( x ) = ( x-1) √ x 6. A particle moves according to s = f ( t ) = t 4-4 t + 1 for t ≥ 0, where t is seconds and s is feet. (a) Find the velocity at time t (b) When is the particle at rest? (c) When is the particle moving in the negative direction? (d) Find the total distance traveled during the ﬁrst 8 seconds....
View Full Document
This note was uploaded on 02/29/2008 for the course MAT 141 taught by Professor Varies during the Spring '08 term at Lehigh University .
- Spring '08